Creating Markets in Kazakhstan : Country Private Sector Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
The first section identifies the overlaps between Kazakhstan's development objectives and the goals of IFC's new strategy of creating markets for the private sector. Kazakhstan's development objectives are to increase diversification, employment, and productivity. These are based on the government's 2030 Strategy and 2020 Plan, as well as World Bank Group (WBG) country assessments. Operationalizing the IFC 3.0 strategy requires identifying the markets with the greatest potential to help meet these objectives. The approach amounts to: (a) identifying those sectors with the greatest market potential which, if realized, would have the greatest impact on development objectives; (b) providing an assessment of what is preventing the realization of market potential; and (c) indicating the IFC and WB activities that should be the top priorities to help meet this double bottom-line of development impact and market creation. The assessment in the second section indicates that the sectors with the greatest unrealized development and market potential are food-grains, meat and poultry, and cross-Kazakhstan transport and logistics. The market potential assessment relies on quantitative tools (multiplier models, product space and competitiveness benchmarking), expert interviews and a survey of policy reports. The assessment in the second section indicates that the sectors with the greatest unrealized development and market potential are food-grains, meat and poultry, and cross-Kazakhstan transport and logistics. The market potential assessment relies on quantitative tools (multiplier models, product space and competitiveness benchmarking), expert interviews and a survey of policy reports. The last section summarizes the priority horizontal reforms, sector-specific policies, and promising sectors with the potential for expansion and greater firm entry. The first part of this section is intended to inform the high-level dialogue between WBG management and Kazakhstani authorities. The second part is essentially the sector-wide measures without which private sector investments will not be forthcoming, recognizing that the aim is to create markets and expand private sector development. The third part identifies promising areas where private sector actors could play a catalytic role, recognizing the ease of playing such roles differs by sector: it is greatest for grains, somewhat less for meat, and least for transport and logistics.